2016
DOI: 10.1007/s00276-016-1682-1
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic study suggests that the morphology of the plantaris tendon may be related to Achilles tendonitis

Abstract: PurposeAchilles tendinopathy is a significant clinical lower limb issue observed in recent years. Neither the location nor the mechanism behind the pain has yet been sufficiently explained. Patients frequently experience pain on the medial side of the calcaneal tendon, and between 2 and 7 cm above the calcaneal tuberosity, which may suggests that the plantaris tendon plays an important role. The purpose of this study was to determine the anatomical relationships between the course of the plantaris tendon and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
97
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 68 publications
(120 citation statements)
references
References 13 publications
(23 reference statements)
7
97
0
2
Order By: Relevance
“…The knee region was dissected using traditional techniques (Olewnik et al, , , , , ). Detailed description of the protocol for dissecting the anterolateral ligament (ALL) in cadaveric specimens . …”
Section: Methodsmentioning
confidence: 99%
“…The knee region was dissected using traditional techniques (Olewnik et al, , , , , ). Detailed description of the protocol for dissecting the anterolateral ligament (ALL) in cadaveric specimens . …”
Section: Methodsmentioning
confidence: 99%
“…In the study carried out by Harvey et al [6] the PM did not occur in 19% of the lower limbs, while Simpson et al [15] concluded that the absence of the PM oscillated between 7% and 20%. In our earlier studies we detected the absence of the PM in 2 out of 50 lower limbs, which represented 4% [12]. …”
Section: Discussionmentioning
confidence: 99%
“…There are several anatomic variations of the PM insertion [2,12,18]. Rare cases of absence of the PM were also recorded [6,12,15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations